The History of the Development and Growth of Arabic Language Science - Neldi Harianto; Rengki Afria; Julisah Izar; Nicolas Habibi (Proceeding International Conference on Malay Identity, 2022)
AbstractThe emergence of the science of Arabic language is the fruit of Islam. Before Islam, there is no historical data that shows evidence of Arab efforts to study Arabic. Apart from the problem of the contact of Arabic with other languages, there were other factors that made the study of Arabic so active at that time. In the case of lahn (solecism; linguistic errors, especially syntax) and the concern of the authorities for the preservation of the language of the Qur'an. The Arabs at that time were also interested in understanding the Qur'an and discovering its meaning. This desire is also shared by non-Arab Muslims who encourage them to learn Arabic and the Qur'an. The purpose of this study is to examine historical data about the history of Arabic linguistics. This research is a literature study with a qualitative descriptive approach, taking data from various references on Arabic linguistics. After studying the data in detail from books on Arabic linguistics, then the data is described by way of narration. From several historical documents of Arabic linguistics it is found that the forerunner of Arabic linguistics which first appeared was nahwu (grammatical) in Basra, and the initial laying of the foundation and formation was carried out by Abu Aswad Adduali (d. 69 H) until the early period of al Khalil bin Ahmad al Farahidi (d. 175 H). Then continued the period of growth and development in Basra and Kufa. Nahwu experts who were influential in this period included al-Khalil bin Ahmad al Farahidi and Abu Ja'far bin Hasan al Ruasi (d. 187 H). until the time of al Mazini al Bashari (d. 249 H) and Ibn Sikkit al Kufiy (d. 243 H). This is followed by a period of maturation and refinement. this period starts from the time of Abu 'Usman al Mazini and Ya'qub bin al Sihhil al Kufi (d. 243 H) to the time of al Mubarrad al Bishri (d. 285 H) and Tsa'lab al Kufi (d. 291 H). The next period is the period of strengthening and writing starting from the III H century to the IV century. Still in the first century of hijriyah, phonetics and lexicography also developed. The first to make this effort was al Khalil bin Ahmad, whose dictionary was entitled al 'Ain. Al Khalil made a dictionary based on sound articulation and showed that the total number of Arabic letters is 29. In the era of Modern Arabic Linguistics, names such as Ali Abd al-Wahid Wafi, professor of sociology at Cairo University, appeared, among others, wrote a book entitled 'Ilm al- Lughah (1941) only after that did linguists at leading Arab universities, especially in Egypt, become interested in studying this science. Wafi's efforts were continued by Ibrahim Anis, professor at the Faculty of Science at Cairo University and Tammam Hasan who wrote Manahij Al Bahts fi al Lughah (1979) and al-Lughah al-Arabiyyah Mabnaha. Keywords: History, Arabic Linguistics